RANCANG BANGUN ALAT UKUR SISTEM MONITORING pH, TEMPERATUR, DAN KELEMBAPAN AKUARIUM IKAN HIAS BERBASIS ARDUINO UNO - Bintara Putra Candra Bareta; Alex Harijanto; Maryani Maryani (Universitas Jember, 2021)
Water quality in the process of ornamental fish cultivation plays an important role in creating an environment of life that is in accordance with the needs of ornamental fish. Acidity (pH) and water temperature are one of the important factors of ornamental fish growth. The purpose of this study is to describe how the design system builds arduino-based humidity and pH temperature measuring instruments. Review the validity of moisture temperature and water pH. Monitor the humidity temperature and pH of ornamental fish aquarium water to know the results of the same data with liturgy. This research is a research and development research, conducted in the Laboratory of Physics Education Study FKIP Jember University. The research time was carried out for four months. The samples used in this study were ornamental carp. Based on the analysis of data obtained, it can be concluded that, (1) The work of pH, temperature, and spouting systems based on Arduino Uno is made with sen0161-V2, DS18B20 and DHT-11 sensors and data appearance media namely LCD. (2) Rakaian system is then calibrated to state that the system can be used properly. Calibration includes Arduino-based pH, temperature and Humidity sensor calibration as well as LCD testing. (3) The data that has been found by the researcher and the data in the literature has a match. Keywords: water quality, Acidity (pH), water temperature, arduino-based.